Change management and strategic planning - Katz, Roberta (Stanford executive briefings, 2006)
Dr Kartz in this program explains six Principles of strategic planning for effective implementation: leadership,clear vision, comprehensive perspective, process for adverse opinions, persistence, and flexibility.